Potency of Chitosan Mouthwash and Gel For Healing Periodontitis Process - Aning Susilowati; Tri Wiyatini (Jurnal Riset Kesehatan, 2014)
The purpose of this research was to identify differences of curing time for gingival bleeding and gingival pocket between the two Chitosan modalities. The study design was Quasi- experimental with pre-post test design. Mouthwash and Chitosan gel formulations were used in the Faculty of Pharmacy Yogyakarta’s laboratory. Respondents were older people in Sari Village, Gadjah Demak Sub-District, and were divided into two groups based on the types of Chitosan used. Respondents were examined and identified their teeth with periodontitis. Measurement of gingival bleeding and gingival pocket depth was done three times, on days 1, 5 and 10. The different categories of gingival bleeding and gingival pocket depth after treatment were then analyzed using Kruskall Wallis Test. The result showed differences in gingival bleeding and gingival pocket depth before and after application of Chitosan gel (p= 0.014, and 0.00, respectively).